Survival versus sustaining: A multidisciplinary inquiryof the environmental dilemma in rural Uganda - Muwanika, Vincent B.; Perry, Mia; Kayendeke, Ellen J.; Pullanikkatil, Deepa; Okot, Alex; Thakadu, Olekae T.; Mwesigwa, Gordon Y.; Mfitumukiza, David (Blackwell Publishing Ltd, 2024)
The livelihoods of the majority of Uganda's population depend on declining environmental resources. The sustainability of the natural environment requires that the people who are interdependent with it, as well as the structures of governance and leadership around them, understand the implications of resource degradation and take deliberate steps towards restoration. The interdependency of human and environment conditions in Uganda requires multidisciplinary attention and this paper reflects a contribution to this end. Socio‐cultural perceptions and relations with a vulnerable environment are put into dialogue with the physical status of environmental resources in Alebtong District, Uganda. Southern epistemological perspectives are considered in relation to Western scientific paradigms. Culturally responsive socio‐cultural research data are related to MODIS NDVI data, using time series analyses and NDVI as a proxy for productivity. The research confirms the declining availability and condition of natural resources and the acknowledgement of local influence on this condition. Despite this, deliberate community and governance efforts towards conservation and restoration varied from non‐existent to insufficient. The causes for this inconsistency revolve around conflicting priorities. This paper demonstrates and discusses the difficult trade‐offs in decision‐making about natural resources that rural communities face, and supports new partnership models as a route to improvement. CrossRef